Chronic inflammatory demyelinating polyneuropathy: quality of life, sociodemographic profile and physical complaints - Patricia Leila dos Santos; Graziela A. Nogueira de Almeida-Ribeiro; Daniele Miguel Daoud Silva; Wilson Marques Junior; Amilton Antunes Barreira (Arquivos de Neuro-Psiquiatria)
Whereas an evaluation of quality of life and possible impacts on the mental state of a patient may help to evaluate the evolution of chronic inflammatory demyelinating polyneuropathy (CIDP), the aim of this study was to study the psychological profile of patients, and evaluate quality of life associated with the disease. Method 41 patients were evaluated using a Mini-Mental State Examination (MMSE) and a Short-Form Health Survey (SF-36). Results The mean age of the patients was 50.6 years, 63.4% men. Of the participants, 65.9% had other health problems, 39% reported needing help with activities of daily living, 49% slept less than 8 hours per night, and 34.1% complained of some memory deficit. The average MMSE score was 26. Impairment of functional capacity and pain were the more important altered health states. Conclusion CIDP has important social and economic impacts, owing to functional impairments that can lead to professional and personal limitations.